2017
DOI: 10.2147/amep.s134235
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance and satisfaction of medical residents utilizing standardized patient versus mannequin-simulated training

Abstract: BackgroundConducting simulations of rapidly decompensating patients are a key part of internal medicine (IM) residency training. Traditionally, mannequins have been the simulation tool used in these scenarios.ObjectiveTo compare IM residents’ performance and assess realism in specific-simulated decompensating patient scenarios using standardized patients (SPs) as compared to mannequin.MethodsNineteen IM residents were randomized to undergo simulations using either a mannequin or an SP. Each resident in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Although some topics are especially suited to a certain approach, many scenarios can, with minor adjustments, be delivered using either an SP or a manikin. Thus far, limited research has explored which option is best in such situations, with previous studies only analyzing specific clinical situations or settings [2,6], and including small sample sizes [5,7]. Hence, we conducted a comparative study to investigate which modality participants responded better to in scenarios that can be run using either an SP or a manikin, in various clinical settings.…”
Section: Introduction Background/rationalementioning
confidence: 99%
“…Although some topics are especially suited to a certain approach, many scenarios can, with minor adjustments, be delivered using either an SP or a manikin. Thus far, limited research has explored which option is best in such situations, with previous studies only analyzing specific clinical situations or settings [2,6], and including small sample sizes [5,7]. Hence, we conducted a comparative study to investigate which modality participants responded better to in scenarios that can be run using either an SP or a manikin, in various clinical settings.…”
Section: Introduction Background/rationalementioning
confidence: 99%
“…Simulation in educational contexts refers to a situation that tries to represent real clinical practice through scenarios with different degrees of fidelity. The use of simulated scenarios allows various clinical skills to be repeatedly trained in a safe environment (Alsaad et al, 2017;Yuan et al, 2012) until an optimal learning level is reached and critical and reflective analysis skills are developed (Hegland et al, 2017;Raurell-Torredà et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional manikin technology is limited in its ability to evoke a sense of immediacy. In fact, researchers found that standardized patients were superior to traditional manikins when teaching clinical deterioration in patients (Alsaad et al, 2017). Nurses may unwillingly miss rescue events when they do not recognize, act on or report signs of clinical deterioration.…”
Section: Concepts Under Considerationmentioning
confidence: 99%